Table of Content - - (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content: 1. Verbal estimates in The Holy Quran and their impact on deriving Fiqh rulings related to worship Dr. Ahmed Abdo Ahmed Al-Ghdarj 2. Towards a national ecosystem to create scientists and sovereign knowledge Dr. Bandar A. Al-Saud , Dr. Abdulhamid A. Al-Abduljabbar 3. Manifestations of religious dialogue between Muslims and Jews Secular Jews as a model Mrs. Maha Dahawi Al-Shamari 4. A study on the Chinese translation Strategies of Arabic Proverbs from the Perspective of Cultural Translation Mrs. Yuan Linxian 5. A pragmatic Analysis of the Interrogative Illocutionary Acts with Reference to Arabic Text of Surah As- Saffat in the Holy Qur’ān Dr. Adel Ahmed Abdullah Al- Mekhlafy , Prof. Abdusalam Mohammed Ghaleb Al- Ghrafy 6. Analysing the Power of Language in a Political Text Mrs. Suhair Adel Abdulamir 7. Application of Abaoub- Shkheam Transform for Solving Linear Partial Integro – Differential Equations Dr. Suad Mawloud Zali 8. Constrained Probabilistic multi-source Continuous Review Inventory Model with Dagum and Kumaraswamy-Dagum distributions Co-Prof. Hala Ali Fergany ,Dr. Amani Saeed Alghamdi , Mrs.Amsha Zayed Almutairi